YUVAL NOAH HARARI’S VIEW ON THE CHALLENGES OF 21st CENTURY EDUCATION - Jiva Agung (ISTORIA: Jurnal Pendidikan dan Sejarah, 2019)
ABSTRACTOne of the aims of formal education is to enable people to live or to work accordingly to the needs of their era. Unfortunately, instead of being used as a tool of living, nowadays learning (particularly History Education) at schools still focuses on memorizing and is far from productive let alone progressive. Yuval Noah Harari, a professor in the History Department of the Hebrew University of Jerusalem, whose trilogy books describe maps out challenges, problems, as well as recommendations for education in the 21st Century so that people of the Century could live their lives properly. This research is a critical review of Yuval Noah Harari’s thoughts about the challenges of 21st Century education. Three monumental Harari’s works (Sapiens, Homo Deus, 21st Lessons) were examined and critically compared with other relevant works. This paper concludes that there are three ways to resolve the problem of education in the 21st Century. First, by relating three periods (past, present, future); secondly, encouraging governments to make positive policies on the three most important issues (nuclear war, environmental crisis, and the disruption of information and technology); and thirdly, inviting the world to participate in solving global problems.Keywords: The 21st Century, Education, Challenges